14.1k views
1 vote
Can someone answer and explain this to me??? thanks!!!!!!!!!!! ​

Can someone answer and explain this to me??? thanks!!!!!!!!!!! ​-example-1
User Torch
by
6.6k points

1 Answer

6 votes

9514 1404 393

Answer:

(f◦g)(x) = x

Explanation:

The composition (f◦g)(x) means f(g(x)). As with any function evaluation, put the argument where the variable is, and simplify.


(f\circ g)(x)=f(g(x))=f\left((3x)/(x-1)\right)=(\left((3x)/(x-1)\right))/(\left((3x)/(x-1)\right)-3)\\\\=(\left((3x)/(x-1)\right))/(\left((3x-3(x-1))/(x-1)\right))=(3x)/(3x-3x+3)=(3x)/(3)\\\\\boxed{(f\circ g)(x)=x}

User Complez
by
5.6k points